Shelf life extension of Saba banana: effect of preparation, vacuum packaging, and storage temperature - Othman, Siti Hajar; Abdullah, Nur Athirah; Nordin, Norhazirah; Abdul Karim Shah, Nor Nadiah; Mohd Nor, Mohd Zuhair; Md Yunos, Khairul Faezah (Elsevier BV, 2021)
The shelf life of banana is very much dependent on the preparation method, packaging method, and storage temperature. Thus, this work is directed to investigate the effect of banana preparation (peeled and unpeeled), packaging method (vacuum packed and non-vacuum packed), and storage temperature (25 and 9 °C) on extending the shelf life of Saba banana. Peeled and unpeeled; and vacuum packed and non-vacuum packed banana was kept at different storage temperatures for 28 days. The shelf life of banana was investigated in terms of texture, color changes, and moisture content every 7 days. It was found that vacuum packed banana samples kept at 9 °C exhibited non-significant changes in firmness, and minimal changes in moisture content and color compared to non-vacuum packed banana kept at 25 °C, proving that vacuum packaging and low storage temperature are promising to extend the shelf life of banana. The unpeeled banana was also demonstrated to exhibit longer shelf life compared to peeled banana because the skin is able to preserve the moisture content inside the banana and prevent the banana to become dried and spoilt over time.